Euthanasia: a dignified death? An ontological perspective - Prada Galvis, Alberto (DIXI, 2024)
For several years now, there has been a discussion in the country about the relevance of euthanasia as a procedure to prevent patients diagnosed with an incurable disease, and in a supreme state of pain and suffering, from having their right to die with dignity violated. Two positions polarize the controversy: those in favor of the procedure and those opposed to it. This article analyzes the discussion, with a journey through the history of euthanasia at the international and national levels, within the framework of specific norms for the Colombian case and the experiences that have been had in this regard. Emphasis is placed on the ontological analysis of euthanasia, considering, in addition, its epistemological nature and a methodological vision. In order to contribute to the discussion, an attempt is made to suggest a conceptual vision regarding the values and underlying purposes of the right to die with dignity, in the context of the Colombian legal system. Substantial aspects such as the bioethical and legal approach, philosophical and sociological support, as well as the implications of a sanitary and political nature, are considered, explaining their relevance in the Colombian legal system. It is concluded that the discussion in its dialectic will continue as long as the Congress of the Republic does not regulate this procedure. At the same time, it is found that assuming the ontology of euthanasia is a task that involves situating oneself in the interpretation of life and death as products embedded in the culture rooted in each context, in the historical vision of these concepts, and in the ideological framework resulting from the transition through the different theories that discuss the process.